Augmenting the formation of esports gameplay intention: interaction effects of genre and gender. Issue 5 (13th August 2021) - Jang, Wooyoung (William); Byon, Kevin K.; Williams, Antonio; Pedersen, Paul M.
Abstract : Purpose: While each genre and gender has been revealed as significant moderators for esports gameplay intention, exploring the interaction effects between genre and gender could broaden our understanding of the drivers' relative effects on esports gameplay intention. Thus, the purpose of this study is to examine the interaction effects of gender and genre in the relationship between esports gameplay intention and its drivers (i.e. hedonic motivation, habit, price value, effort expectancy, social influence and flow). Design/methodology/approach: The hypothesized model was examined using data from a sample ( N  = 1, 194). For the purposes of data analysis, confirmatory factor analysis and structural equation modeling were used to examine the hypothesized model. Then, a series of structural invariance tests were conducted to compare the interrelationship between the six determinants and esports gameplay for the six-group model. Findings: The results of the six-group model comparison indicated that the interaction between gender and genre moderates the relationship between drivers and esports gameplay intention. In particular, the following moderation effects were observed: (1) "social influence-esports gameplay intention" between "male-physical enactment" and "female-physical enactment"; (2) "habit-esports gameplay intention" and (3) "effort expectancy-esports gameplay intention" between "female-imagination" and "female-physical enactment"; (4) "hedonic motivation-esports gameplay intention" and (5) "effort expectancy-esports gameplay intention" between "female-physical enactment" and "female-sport simulation." Originality/value: The findings of this current study contributed to clarifying the genre and gender effects in esports gameplay intention and thus the extension of the Esports Consumption (ESC) model (Jang et al., 2020a) and the technology adoption literature. Since the ESC model grounded the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), the improvement of the ESC model extended UTAUT2. In consumer behavior research in the esports context, this current study contributed to the extension of UTAUT2 on the new moderating mechanisms by adding the interaction between gender and esports game genre.